Avaliação da toxicidade de florações naturais e de cultura de cianobactérias: efeitos sobre Ceriodaphnia silvestri (Crustacea, Cladocera) - Mendonça, Juska Milena dos Santos (2006)
The incidence of toxic cyanobacterial blooms is one of the important consequences of eutrophication in aquatic ecosystems. It is a very common phenomenon in reservoirs and shrimp ponds in the State of Rio Grande do Norte (RN), Brazil. Cyanobacterias produce toxins which can affect aquatic organisms and men trough the food chain. Aiming to contribute to the studies of cyanobacterias in RN, we propose: a) to evaluate the toxicity of isolated cyanobacterias in important fresh-water environments; and b) to verify the effects of both natural and cultured blooms occurred in reservoirs for human supply and in the cladoceran Ceriodaphnia silvestrii. This study was carried out using samples of natural blooms occurred between March and October of 2004 in Gargalheiras Dam (08º L e 39º W), in July of 2004 in Armando Ribeiro Gonçalves Dam (06o S e 37o W) and in commercial shrimp ponds (Litopenaeus vannamei) located in fresh-water environments. The samples were collected with plankton net (20µm.) for identification, isolation and obtaining of phytoplanktonic biomass for liophilization and later toxicity bioassays. The toxicity of cultured samples and natural blooms was investigated through bioassays in Swiss mice. Quantification of cyanobacteria in samples was conducted following the Ütermol method, with 300mL samples fixed with lugol. The toxicity test with Ceriodaphnia silvestrii followed ABNT, 2001 recommendations, and were accomplished with natural hepatotoxic bloom s samples and cultured samples of both non-toxic and neurotoxic C. raciborskii. In this test, five newborns, aged between 6 and 24 hours, were exposed to different concentrations (0 a 800 mg.L-1) of crude cyanobacterial extracts during 24 and 48 hours. Three replicates were used per treatment. The pH, temperature and dissolved oxygen at the beginning and after 24 and 48hours from the test were measured. We estimated the CL50 through the Trimmed Spearman-Karber method. The blooms were constituted by Microcystis panniformis, M. aeruginosa, Anabaena circinalis, Cylindrospermopsis raciborskii and Planktothrix agardhii, producers of mycrocistin-LR confirmed with HPLC analysis. Samples of hepatotoxic blooms registered toxinogenic potential for C. silvestrii, with CL50-24h value of 47.48 mg.L-1 and CL5048h of 38.15 mg.L-1 for GARG samples in march/2005; CL50-24h of 113,13 mg.L-1 and CL5048h of 88,24 mg.L-1 for ARG July/2004; CL50-24h of 300.39 mg.L-1 and CL50-48h of 149.89 mg.L-1 for GARG October/2005. For cultured samples, values of CL50-24h and CL50-48h for C. raciborskii toxic strains were 228.05 and 120.28 mg.L-1, respectively. There was no mortality of C. silvestrii during the tests with non-toxic C. raciborskii strain. The toxicity test with C. silvestrii presented good sensitivity degree to cyanotoxins. The toxicity of natural hepatotoxic blooms samples (microcystins) and cultured neurotoxic saxitoxins producer samples analyzed in this study give us strong indications of that toxin s influence on the zooplanktonic community structure in tropical aquatic environments. Eleven cyanobacteria strains were isolated, representing 6 species: Anabaenopsis sp., Cylindrospermopsis raciborskii, Chroococcus sp., Microcystis panniformis, Geitlerinema unigranulatum e Planktothrix agardhii. None presented toxicity in Swiss mice. The strains were catalogued and deposited in the Laboratório de Ecologia e Toxicologia de Organismos Aquáticos (LETMA), in UFRN, and will be utilized in ecotoxicológical and ecophysiological studies, aiming to clarify the causes and control of cyanobacterial blooms in aquatic environments in RN. This state s reservoirs must receive broader attention from the authorities, considering the constant blooms occurring in waters used for human consumption